-7(k+3)-(-8k+7)=5

Simple and best practice solution for -7(k+3)-(-8k+7)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(k+3)-(-8k+7)=5 equation:


Simplifying
-7(k + 3) + -1(-8k + 7) = 5

Reorder the terms:
-7(3 + k) + -1(-8k + 7) = 5
(3 * -7 + k * -7) + -1(-8k + 7) = 5
(-21 + -7k) + -1(-8k + 7) = 5

Reorder the terms:
-21 + -7k + -1(7 + -8k) = 5
-21 + -7k + (7 * -1 + -8k * -1) = 5
-21 + -7k + (-7 + 8k) = 5

Reorder the terms:
-21 + -7 + -7k + 8k = 5

Combine like terms: -21 + -7 = -28
-28 + -7k + 8k = 5

Combine like terms: -7k + 8k = 1k
-28 + 1k = 5

Solving
-28 + 1k = 5

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '28' to each side of the equation.
-28 + 28 + 1k = 5 + 28

Combine like terms: -28 + 28 = 0
0 + 1k = 5 + 28
1k = 5 + 28

Combine like terms: 5 + 28 = 33
1k = 33

Divide each side by '1'.
k = 33

Simplifying
k = 33

See similar equations:

| 2+3x-5x=-4 | | 16(x-9)=4(2a-x) | | -6(u+6)=4u+4 | | 1/4t+3/5=2/5-t | | -7x+3-5x=-57 | | 8+28m-24-12m=0 | | -34=5x+3(x+2) | | f(x)=a(x+3)(x+1)(x-4) | | 5y-7x=12 | | 6x^2+3xy+3y^2=108 | | x=-1.5+0.5y | | -3t^2+16t-11=0 | | 16x^2+64t+64=0 | | 6-2x(3-12)=2x+90 | | 20x+5=-2x | | 3(u-5)-6u=-33 | | 0.4-8.1y-2.7y=1-10.8y-0.6 | | 11(k-2)+[k-3(k+1)]=0 | | (3c-8)(3c-8)=0 | | y=-3+2y | | 7(y+2)-5y=-4 | | 8-28m-24-12m=0 | | 2(t-1)+3t=2 | | -2(d+6)=-20 | | 2*j=25+j | | K-(-40)=32 | | 2t-4=2 | | 36=4(8x+1) | | 3(w+7)=-3 | | 8(1-4x)+8(x+3)=32 | | 8(1-4x)+8(m+3)=32 | | 4(0+1)=4(x+8) |

Equations solver categories